The Amarna Diplomacy in IR Perspective – A System of States in the Making: A diplomacia de Amarna e as Relações Internacionais: um sistema de estados em construção - Aissaoui, Alex (Estudos Internacionais: revista de relações internacionais da PUC Minas, 2018)
The Amarna diplomacy (ca. 1365–1330 BCE) has been of interest for specialists ever since the discovery of the Amarna letter collection in the late 19th century. While it can be considered as one of the great archaeolo-gical discoveries of all time, it has largely remained out of academic purview in the field of International Relations (IR). IR scholarship continues to turn to the Greco-Roman experience in its attempt to delineate the chronological framework of the discipline. Far from being an anecdote in international history, this article aims to analyze what the letters convey for a student of world politics. What comes out of these missives through textual analysis of the primary sources is not only the various demands, wishes and security concerns of the actors involved but also classical IR themes such as power balancing, security dilemma and international anarchy. While there are question marks and lacunas, this paper asserts that the ancient Near Eastern world constituted an international arena where we see the makings of a genuine system of states more than a millennium before the writings of Thucydides. The Amarna letters, although incomplete, are a gateway to gain deeper synergy between IR theory and international history.